(untitled) (Bangladesh Journal of Agricultural Research, 2022)
The experiment was conducted at Dobila, Tarash of Shirajgonj in Chalan Beel during rabi season of 2016-17 and 2017-18. The treatments were four wheat varieties viz. ‘BARI Gom-25’, ‘BARI Gom-26’, ‘BARI Gom-28’ and ‘BARI Gom-30’. Wheat var. ‘BARI Gom-30’ produced the highest grain yield (5.02 t/ha in 2016-17 and 4.83 t/ha in 2017-18 with pooled value of 4.93 t/ha) associated with higher number of spikes/m2 (372-444/m2 with pooled value of 408/m2) and higher number of grains/spike (pooled value of 45/spike). ‘BARI Gom-30’ required field duration of 113 days. Two years’ results revealed that ‘BARI Gom-30’ performed better in Chalan Beel area in respect of higher mean grain yield (4.93 t/ha) and economics (Gross margin of Tk.100400/ha and BCR of 1.78). There was no blast infestation in the experimental field in both the years. Farmers showed moderate interest to grow wheat in Chalan Beel area specially in upland (medium low land of Beel) condition. Among the wheat variety ‘BARI Gom-30’ could be suitable for cultivation in Chalan Beel area. Bangladesh J. Agril. Res. 45(1): 21-27, March 2020